Prosodi Tuturan Penolakan dalam Drama Oosama no Resutoran Karya Koki Mitani - Nani Surnani; Ekaning Krisnawati; Fahri Delfariyadi (Jurnal Sosioteknologi, 2023)
The refusal act is one of the essential speech acts in the linguistic realm. Refusal is not confined to verbal action; it also has physical properties, exhibited by its prosodic structure. The present study discusses the prosody of the refusal act in the Oosama no Resutoran drama and employs a qualitative descriptive method. The refusal act that was taken from the drama is used as the data. The Praat application is utilized in the analysis stage. The findings show that intonation and pitch are intertwined. A further discovery is that emotion influences the realization of the refusal act, which is manifested by thelingual markers.